Landscape of Pin1 in the cell cycle. (March 2015) - Lin, Cheng-Han; Li, Hao-Yi; Lee, Yu-Cheng; Calkins, Marcus J; Lee, Kuen-Haur; Yang, Chia-Ning; Lu, Pei-Jung
Pin1 is a peptidyl-prolyl isomerase which plays a critical role in many diseases including cancer and Alzheimer's disease. The essential role of Pin1 is to affect stability, localization or function of phosphoproteins by catalyzing structural changes. Among the collection of Pin1 substrates, many have been shown to be involved in regulating cell cycle progression. The cell cycle disorder caused by dysregulation of these substrates is believed to be a common phenomenon in cancer. A number of recent studies have revealed possible functions of several important Pin1-binding cell cycle regulators. Investigating the involvement of Pin1 in the cell cycle may assist in the development of future cancer therapeutics. In this review, we summarize current knowledge regarding the network of Pin1 substrates and Pin1 regulators in cell cycle progression. In G1/S progression, cyclin D1, RB, p53, p27, and cyclin E are all well-known cell cycle regulators that are modulated by Pin1. During G2/M transition, our lab has shown that Aurora A suppresses Pin1 activity through phosphorylation at Ser16 and cooperates with hBora to modulate G2/M transition. We conclude that Pin1 may be thought of as a molecular timer which modulates cell cycle progression networks.